Fracture of Wedge-Shaped Body Under Compression - Leonid Yu. Stupishin; Konstantin E. Nikitin; Alexander V. Masalov (Structural Mechanics of Engineering Constructions and Buildings)
The aim is to study the fracture process of a wedge-shaped body during compression. A large number of researchers have turned to the classical solution of the elasticity theory problem of the loaded wedge-shaped body, but the problem of a supported wedge of a finite shape still has no analytical solution. The authors conducted a study of the failure mechanism of such bodies by both computational and experimental methods. To carry out the numerical analysis, the implementation of the progressive limit state method at critical levels of strain energy in the form of the force method was used, in combination with the method of approximation of continuum by an equivalent truss. The equivalent truss model of the wedge used here clearly demonstrates the process of removing structural members due to them reaching limit states. The technique of progressive limit states, based on the consecutive identification of “weak links” in the structure, in which the limit state occurs first, made it possible to construct fracture models of the considered body. The results of the performed analysis are presented in the form of fracture models of wedge-shaped bodies. The failure mechanism of wedge-shaped bodies was also investigated by experimental methods. Wedge-shaped gypsum specimens were compressed at the tip of the wedge and brought to fracture. The differences between the obtained fracture patterns and the classical results known from the theory of elasticity obtained for infinite wedge-shaped bodies are shown. A comparison of experimental and numerical results is performed, and a conclusion is made about the real fracture patterns of wedge-shaped bodies with a supported part.